"SMART DRIP IRRIGATION SYSTEM" SISTEM IRIGASI TETES TERKENDALI PADA TANAMAN TEMBAKAU - Shofi, Alfi Baqiatus; Aufa, Jaza’an; Fajaruddin, Muhammad; Fadilah, Shofwatul; Fawzi, Yustafat (Program Kreativitas Mahasiswa - Teknologi, 2014)
Smart drip irrigation System is a drip irrigation system that controlled by microcontroller which would be applied on tobacco plantation cooperated with PTPN X Klaten. Nowadays, the drip irrigation system has been applied by PTPN X but the result is not maximal comparing with conventional irrigation system. The application of smart irrigatin system intended to automate and determine the precision schedule of irrigation so definitely the plant water need will be known. The utilization of precision schedule of irrigation system would give us the maximum result of the plant, because the soil moisture was able to maintain at the available moisture condition so the plant growth is better. In addition to water usage is more efficient because the water was given exactly to the root zone then percolation and run-off were able to prevent so the operating cost of diesel pump is cheaper. Smart drip irrigation is a combination from drip irrigation system and control system which equipped with soil moisture sensors to detecting the plant water needs approach the soil moisture on the wilting point (TL) and field capacity (KL) condition were then being a feedback to control system to activate and deactivate the pump in the irrigation system. The automatic irrigation system is activated if the soil moisture below the wilting point and deactivated if the soil moisture above the field capacity.Keywords: automatic irrigation, the scheduling irrigation, microcontroller, field capacity (KL), wilting point, smart drip irrigation system